Predictors of poor outcomes in patients with intracerebral hemorrhage - Liling Zeng; Qixin Zhang; Zhangyong Xia; Wanzhen Cui; Jianwen Guo (Frontiers in Neurology)
ObjectiveTo identify the predictors of 3-month outcomes in Chinese patients with intracerebral hemorrhage (ICH) receiving conservative management.MethodsFrom October 2013 to May 2016, a total of 5,589 individuals with ICH were screened as part of the CRRICH study (Clinical re-evaluation of removing blood stasis therapy in treating acute intracerebral hemorrhage). Of these, 319 patients were ultimately enrolled. This study constitutes a post analysis of the CRRICH study. Potential predictors of poor outcomes following spontaneous ICH, initially identified through univariate analysis, were further evaluated using an unconditional multiple logistic regression model. Poor outcomes were defined as a modified Rankin scale score > 2 at 90 days post-ICH.ResultsOf the 319 patients (mean age 62.46 ± 0.71 years; male/female ratio 1.8:1), 89 (27.9%) had poor 3-month outcomes. Multivariable analysis showed increased odds of poor outcomes with older age (odds ratio [OR] 1.05; 95% confidence interval [CI] 1.02–1.08; p < 0.001), right hemispheric hemorrhage (OR 2.41; 95% CI 1.26–4.60; p = 0.008), intraventricular hemorrhage (OR 3.70; 95% CI 1.80–7.61; p < 0.001), and a higher National Institutes of Health Stroke Scale score (NIHSS) (OR 1.21; 95% CI 1.14–1.29; p < 0.001). Conversely, higher body mass index (BMI) (OR 0.88; 95% CI 0.77–0.99; p = 0.015) and shorter symptom-to-admission time (OR 0.77; 95% CI 0.62–0.97; p = 0.025) were associated with reduced odds of poor outcomes.ConclusionIn conservatively treated ICH patients, right hemispheric involvement, ventricular hemorrhage, older age, and higher NIHSS score increased poor outcome risks at 3 months, while higher BMI and early admission reduced risks, aiding clinical prognosis prediction.